2015
DOI: 10.1093/jme/tjv051
|View full text |Cite
|
Sign up to set email alerts
|

Aedes aegypti(Diptera: Culicidae) in Mauritania: First Report on the Presence of the Arbovirus Mosquito Vector in Nouakchott

Abstract: Aedes aegypti L. (Diptera: Culicidae) is a major vector of yellow fever, dengue, and chikungunya viruses throughout tropical and subtropical areas of the world. Although the southernmost part of Mauritania along the Senegal river has long been recognized at risk of yellow fever transmission, Aedes spp. mosquitoes had never been reported northwards in Mauritania. Here, we report the first observation of Aedes aegypti aegypti (L.) and Aedes (Ochlerotatus) caspius (Pallas, 1771) in the capital city, Nouakchott. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 13 publications
1
21
0
3
Order By: Relevance
“…This observation is consistent with the results of the studies that reported that saltwater tolerant mosquito larvae can develop normally in both fresh and saline habitats [52]. The presence of both fresh and brackish larval habitats in Nouakchott is the result of artificial (man-made) and natural (rainfall and rising goundwater) factors [11,12]. During the past decade, a succession of dry years (2012, 2015 and 2017) and humid years, with sometimes heavy rainfall (floods in 2013 and 2016), occurred in Nouakchott (National Meteorological Office, unpublished data).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This observation is consistent with the results of the studies that reported that saltwater tolerant mosquito larvae can develop normally in both fresh and saline habitats [52]. The presence of both fresh and brackish larval habitats in Nouakchott is the result of artificial (man-made) and natural (rainfall and rising goundwater) factors [11,12]. During the past decade, a succession of dry years (2012, 2015 and 2017) and humid years, with sometimes heavy rainfall (floods in 2013 and 2016), occurred in Nouakchott (National Meteorological Office, unpublished data).…”
Section: Discussionsupporting
confidence: 91%
“…Anopheles arabiensis is widely distributed in the Sahelian as well as the Saharan zone of the country [7,9,10]. Moreover, previous studies have shown that it is the only malaria vector encountered in Nouakchott [11,12]. In this urban area, An.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of early 2019, no reports could be found that have identified chikungunya in the northeast bordering nation of Mauritania, although the Ae. aegypti mosquito is known to be endemic there [37]. Additionally, in Senegal, CHIKV studies have tended to be concentrated in the sparsely populated southeastern region of Kedougou, bordering Mali [19], meaning that no estimates are available for the northern regions of Senegal or the nomadic pastoralist population.…”
Section: Discussionmentioning
confidence: 99%
“…Aedes aegypti is the main vector of yellow fever, dengue, chikungunya, and Zika virus in all tropical and subtropical areas of the planet [1,2]. According to the World Health Organization [3], dengue is a viral disease with greater spread transmitted by mosquitoes over the last 50 years and infects around 50 to 100 million people annually, exposing the risk of death to almost half of the world population in regions endemic of the virus [4].…”
Section: Introductionmentioning
confidence: 99%